Brand Activism Strategies to Enhance Brand Perception: A Case Study of Environmental Activism at Manualle - Roadiastuty, Augita Putri Roadiastuty (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
The awareness of the society to start caring about environmental impacts raises the demands on the industry to be able to carry out more responsible business activities. This demand encourages the emergence of brand activism, where the brands take a stand, involve consumer aspirations and carry out economic actions that are more concerned about the interests of common life apart from profit orientation. This research took qualitative data using focus group discussion interviews through purposive sampling with an open questionnaire, to find data that could represent consumer perceptions of brand activism, especially environmental activism of Manualle. After conducting three FGD sessions, 15 people FGD participants in Mei 2022, processing primary data in the form of audio and video into verbatim text, conducting open coding, axial coding and selective coding using Atlas.ti, the analysis of this study showed that Manualle has appeared to be doing environmental activism and becoming a recommended brand in Indonesia. Participants of this study further see Manualle as a potential brand, so it is expected to be able to drive change in the future, the first step of which can be done through managerial implementation in the company's internals, both in terms of product development, expanding environmental activism and marketing. The results of this research also found steps that can be applied as an evaluation and optimization of branding through brand activism strategy.